Re: Differential Calculus - Complex solutions

Your simplification is wrong

$\displaystyle \displaystyle \begin{align*} iz + z &= 0 \\ i(x + iy) + x + iy &= 0 + 0i \\ ix - y + x + iy &= 0 + 0i \\ x - y + i(x + y) &= 0 + 0i \end{align*}$

Now equating real and imaginary parts gives

$\displaystyle \displaystyle x - y = 0$ and $\displaystyle \displaystyle x + y = 0$.

So the solutions are $\displaystyle \displaystyle y = x$ and $\displaystyle \displaystyle y = -x$.

Re: Differential Calculus - Complex solutions

Quote:

Originally Posted by

**madbandlt** Hey guys, quick question

(b) Find all complex solutions of iz + z = 0 and sketch them in the complex plane.

Well I let z = x + iy, simplified and obtained x - y + i(x - y) = 0

But as for sketching them I'm not entirely sure how to proceed. The answers have up and until the answer I obtained but then immediately proceeds to sketching y = x

Can someone please explain why y = x is the solution?

The equation i z + z = (1+i) z = 0 is first degree algebrical and its only solution is z=0...

Kind regards

$\displaystyle \chi$ $\displaystyle \sigma$

Re: Differential Calculus - Complex solutions

Quote:

Originally Posted by

**Prove It** Your simplification is wrong

$\displaystyle \displaystyle \begin{align*} iz + z &= 0 \\ i(x + iy) + x + iy &= 0 + 0i \\ ix - y + x + iy &= 0 + 0i \\ x - y + i(x + y) &= 0 + 0i \end{align*}$

Now equating real and imaginary parts gives

$\displaystyle \displaystyle x - y = 0$ and $\displaystyle \displaystyle x + y = 0$.

So the solutions are $\displaystyle \displaystyle y = x$ and $\displaystyle \displaystyle y = -x$.

The equations $\displaystyle \displaystyle x - y = 0$ and $\displaystyle \displaystyle x + y = 0$ have to be true simultaneously. Therefore the only solution is x = y = 0.

But the OP has not actually typed the correct question. The correct question is probably the following:

Find all complex solutions of $\displaystyle iz + \overline{z} = 0$ and sketch them in the complex plane.

In which case, you end up with the two equations x - y = 0 and x - y = 0 and the solution is obviously y = x.